The Use of Snakes and Ladders Game to Improve Studentsâ€™ Grammar at the Second Grade of Mts DDi Baru - Devi Triani; Rabiatul Adawiah; Nihla Afdaliah (Borneo Educational Journal (Borju), 2023)
The second graders of MTs DDI Baru face several issues in learning English. Those become obstacles for them to get good achievement in the subject. One of the most difficult issue for them is they could not even compose a simple sentence properly using basic tenses such as simple present and simple past tense. The researcher tried to use game-based learning, in this case, using Snakes and Ladders game to solve the problem. So that, this research aims to find out the significant effect of using of snakes and ladders game in improving studentsâ€™ grammar ability. This research design applied research with one pre-test and one post-test design in the experimental and control class. From 5 classes, the researcher chose 2 classes as sample by using cluster random sampling. The data analysis result revealed that the post-test mean score (74.07) is greater than the pre-test mean score (37.24) in experimental class. The results of the t-test also confirm that the p-value is 0.001, or smaller than 0.05, whereas the t-value is 8.87 or greater than t-table 2.048. So, by considering the p and the t value, the reseacher withdraw conclusion that Hâ‚ is accepted which states that the use of the Snakes and Ladders game can improve studentsâ€™ grammar. However, another interesting finding reveals that there is also improvement of studentsâ€™ scores in the control class but not as significant as in the experimental class. The mean score increased 15.86 points while in the experimental class it increased 36.83 points